FORMULASI TEPUNG KOMPOSIT KELADI DAN UBI JALAR SEBAGAI BAHAN BAKU MI KERING PENGGANTI SEBAGIAN TERIGU - Fawzan Sigma Aurum; Dian Adi Anggraeni Elisabeth (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2015)
ABSTRACTFormulation of Taro and Sweet Potato Composite Flours as Partly Substitution of Wheat Flour in Dried Noodle Making. Taro and sweet potatoes may address food diversification to reduce dependency on wheat flour. This research aimed to determine the best proportion of taro (Colocasia esculenta (L.) Schott) and sweet potato (Ipomoea batatas L.) composite flours as partly substitution of wheat flour in dried noodle making based on sensory, physical, and chemical characteristics. The research was conducted in July 2013 in the Postharvest Laboratory of Bali AIAT. In the making of dried noodle, 30% composite flours was replacing wheat flour. Research used Completely Randomized Design (CRD) with 7 treatments of flours proportion and 3 replications per each treatment. Data was analysed using Anova followed by DMRT at 5%. Dried noodle’s characteristics observed included organoleptic properties (color, aroma, flavor, texture, firmness, stickiness), chemical properties (water, ash, protein, fat, carbohydrate) and physical properties (rehydration time, water absorption, solid loss due to cooking). The results showed that composite flours of taro and sweet potato could substitute 30% wheat flour in the making of dried noodle. The best proportion of composite flours for 30% wheat flour substitution consisted of 80% taro flour and 20% sweet potato. The chemical content of the best dried noodle was, respectively, water 7.30%, ash 1.66%, protein 7.10%, fat 0.32%, and carbohydrate 83.64%; with the physical properties as follow: optimum rehydration time at 3 minutes, water absorption at 318.15% and solid loss due to cooking at 4.31%. Keywords: Taro, sweet potato, flour, physical properties, chemical propertiesABSTRAKTepung keladi dan ubi jalar berpotensi untuk mengganti sebagian kebutuhan tepung terigu yang hingga kini masih bergantung pada impor. Penelitian ini bertujuan untuk mendapatkan proporsi tepung komposit keladi (Colocasia esculenta (L.) Schott) dan ubi jalar (Ipomoea batatas L.) yang terbaik sebagai pengganti sebagian terigu untuk bahan baku mi kering berdasarkan karakteristik sifat sensoris dan fisiko-kimianya. Penelitian dilakukan pada Juli 2013 di Laboratorium Pascapanen BPTP Bali. Proses pembuatan mi kering, 30% terigu disubtitusi dengan tepung komposit keladi dan ubi jalar. Percobaan menggunakan Rancangan Acak Lengkap (RAL) dengan 7 perlakuan formulasi tepung komposit keladi dan ubi jalar dan 3 ulangan. Data dianalisis dengan ANOVA dilanjutkan dengan uji DMRT pada taraf 5%. Karakterisasi yang diamati meliputi sifat organoleptik (warna, aroma, rasa, tekstur, kekenyalan, kelengketan), sifat kimia (air, abu, protein, lemak, karbohidrat) dan sifat fisika (waktu rehidrasi, daya serap air, kehilangan padatan akibat pemasakan (KPAP). Hasil penelitian menunjukan bahwa tepung komposit keladi dan ubi jalar dapat mensubtitusi 30% terigu dalam pembuatan produk mi kering, dimana proporsi terbaik tepung komposit adalah 80% tepung keladi dan 20% tepung ubi jalar. Mi kering terbaik tersebut memiliki kadar air 7,30%, kadar abu 1,66%, kadar protein 7,10%, kadar lemak 0,32%, dan kadar karbohidrat 83,64%; dengan waktu optimum pemasakan adalah 3,0 menit, DSA 318,15% dan KPAP 4,31%. Kata kunci: Keladi, ubi jalar, tepung, sifat fisika, sifat kimia